Development of a STEM-Based Activity Sheet to Train Critical Thinking in Reaction Rates - Ardianti Dwi Agustin; Berta Yonata (Hydrogen: Jurnal Kependidikan Kimia, 2026)
This study aims to develop a feasible STEM-based Student Activity Sheet on reaction rate material to train students’ critical thinking skills, based on aspects of validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using 4D model, which encompasses four sequential phases: define, design, develop, and disseminate. However, the implementation of this study is confined to the develop stage. The product was validated by two chemistry education experts and one chemistry teacher to assess content and construct validity. The practicality was evaluated through student response questionnaires and observation sheets, while its effectiveness was measured using pretest and posttest scores of critical thinking skills and learning outcomes analyzed through the N-Gain formula. The validation results showed a mode score of 4, which in valid category. The practicality test yielded a score of 92% from student responses and 97% from observation results, categorized as very practical. The effectiveness analysis demonstrated that most students achieved high N-Gain scores (g ≥ 0.7) in critical thinking indicators, with a significant improvement in learning outcomes from an average pretest score of 63 to a posttest score of 85. These findings indicate that the developed STEM-based LAPD is valid, practical, and effective to train students’ critical thinking skills on reaction rate material.